2021
DOI: 10.3389/fmicb.2021.741875
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis for High- and Low-Aflatoxin-Yield Aspergillus flavus Strains Isolated From Natural Environments

Abstract: The molecular mechanisms underlying aflatoxin production have been well-studied in strains of the fungus Aspergillus flavus (A. flavus) under artificial conditions. However, aflatoxin biosynthesis has rarely been studied in A. flavus strains isolated from field conditions with different aflatoxin-producing ability. In the present study, tandem mass tag (TMT) labeling and high-performance liquid chromatography (HPLC) coupled with tandem-mass spectrometry analysis were used for proteomic quantification in natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Thus, we perform a TMT-labeled quantitative lysine succinylome to comprehensively report the changes in Ksuc levels between high and low AF production strains of A. flavus isolated under natural conditions. From our quantitative global proteomics data, we noticed that the upregulated proteins in the high AF yield group were mostly enriched in carbon-related metabolism, whereas the downregulated proteins were enriched in oxidative phosphorylation; through subsequent functional analysis, we found that the upregulated proteins involved in carbon-related metabolism had a direct relationship with AF production ( 48 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, we perform a TMT-labeled quantitative lysine succinylome to comprehensively report the changes in Ksuc levels between high and low AF production strains of A. flavus isolated under natural conditions. From our quantitative global proteomics data, we noticed that the upregulated proteins in the high AF yield group were mostly enriched in carbon-related metabolism, whereas the downregulated proteins were enriched in oxidative phosphorylation; through subsequent functional analysis, we found that the upregulated proteins involved in carbon-related metabolism had a direct relationship with AF production ( 48 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, all protein samples were obtained from our previous global proteomics protein preparation and prepared from a single experiment ( 48 ). In detail, 10 6 conidia was inoculated into liquid YES media and shaken at 180 revolutions/min for 5 days at 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Employing tandem mass tag (TMT)-labeled quantitative lysine succinylome, they extensively documented the variations in Ksuc levels between A. flavus strains exhibiting high and low aflatoxin production under natural conditions. Subsequent functional analysis revealed a direct correlation between the upregulated proteins involved in carbon-related metabolism and aflatoxin production [147].…”
Section: Lysine Succinylation In Fungimentioning
confidence: 99%
“…The last stage of AFB1 production is the conversion of sterigamtocystin into aflatoxin B2. The conversion of sterigamatocystin into O–methylsterigmatocystin (OMST) is catalyzed by an O-methyltransferase encoded by the aflP ( omtA ) gene, whose expression is highly influenced by the growth conditions [ 310 , 311 ]. The A-ring of O–methylsterigmatocystin (OMST) is oxidized, and an intermediate named 11-hydroxy-O-methylsterigmatocystin (HOMST) is formed.…”
Section: Significance Of Fungi In Different Sectorsmentioning
confidence: 99%